Case report: A rare case of Leclercia adecarboxylata bacteremia in an immunocompetent psychiatric patient: exploring the links between mental health and infectious diseases - Yan, Fei; Ruan, Xi; Tang, Qin; Song, Guo Lin; Xie, Ren Fang; Bao, Xing Chen (Frontiers in Immunology, 2024)
This study aims to explore the pathogenic potential of Leclercia adecarboxylata as a rare pathogen in immunocompetent individuals and to analyze how mental health status may influence susceptibility to infection. We report a case of bacteremia in a 31-year-old immunocompetent female who developed L. adecarboxylata infection during an episode of severe depression. Although the patient exhibited self-harm tendencies, a thorough physical examination did not reveal any external wounds or signs of injury. This case demonstrates that, despite the absence of obvious external infection sources, invasive procedures, or visible trauma, L. adecarboxylata can induce severe bacteremia in immunocompetent individuals. The patient presented with high fever and systemic inflammatory response, with blood cultures confirming the presence of L. adecarboxylata, and chest imaging showing bilateral lower lobe inflammation. Following treatment with ceftriaxone, the patient’s symptoms rapidly improved, and infection markers normalized. This study elucidates the potential mechanisms by which L. adecarboxylata can cause infection in immunocompetent individuals and examines the influence of mental health on infection susceptibility. It provides new insights into the complex relationship between mental illness and infection, highlighting the need for further investigation into how mental health may affect infection risk and its clinical management. In conjunction with existing research, this study discusses how psychological stress and behavioral patterns may increase infection risk and recommends future research to further explore the interplay between mental disorders and infectious diseases.